Brentuximab vedotin plus chemotherapy for the treatment of front-line systemic anaplastic large cell lymphoma: subgroup analysis of the ECHELON-2 study at 5 years’ follow-up - Domingo-Domènech, Eva; Pro, Barbara; Illidge, Tim; Horwitz, Steven; Trumper, Lorenz; Iyer, Swami; Advani, Ranjana; Bartlett, Nancy L.; Christensen, Jacob Haaber; Kim, Won-Seog; Feldman, Tatyana; Choi, Ilseung; et al. (Blood cancer journal (New York), 2025)
Trial registration: ClinicalTrials.gov number: NCT01777152